Organizational Responses to Issues Concerning the Delegation of Authority in Situations Involving Public Participation - Goldenberg, Sheldon (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1984)
The delegation of authority presents ideological and structural problems for organizations implementing programmes of public participation. Two specific ideological fallacies are examined as these embody rationalizations for opposition to public involvement in decision-making and at most only the “mechanistic” incorporation of public participation bureaus within existing organizations. Since effective public participation requires a flexible organization that can respond quickly, directly and authoritatively in interaction with local resident groups, and mechanistic bureaucracies can do none of these, this organizational structuring guarantees the failure of public participation. It is therefore suggested that those organizations that wish to engage in meaningful and useful public participation programmes will have to alter their internal organizational structures in the direction of the “organic” type.